Neolithic and Paleometal Epoch Materials from the Bazyakovo I Campsite at the Mouth of the Kama River - Anton V. Shipilov (Археология евразийских степей)
The article deals with the materials of one of the multi-complex settlement monuments, the Bazyakovo I campsite, located at the mouth of the Kama River. The purpose of the work is to introduce into scientific discourse an array of archaeological sources of the campsite under consideration. In its materials, obtained as a result of archaeological studies, several stages of functioning can be traced. The earliest stage is associated with the Kama Neolithic culture. In addition to ceramics, it includes a very expressive collection of stone tools, obtained as a result of studies at the archaeological site under consideration. A large number of woodworking tools should be noted. The finds, related to the Kama culture, may be partially synchronized with the dotted-and-combed wаre. In later times, the territory of the campsite was occupied by bearers of ceramics of the Novoilyinka culture. In the Late Eneolithic, the site of the monument was occupied by the population of the Garino culture. The campsite continued to exist in the Late Bronze Age. The final stage of its functioning falls on the Early Iron Age.